Synthesis and Human Carbonic Anhydrase I, II, IX, and XII Inhibition Studies of Sulphonamides Incorporating Mono-, Bi- and Tricyclic Imide Moieties - Kalyan K. Sethi; KM Abha Mishra; Saurabh M. Verma; Daniela Vullo; Fabrizio Carta; Claudiu T. Supuran (Pharmaceuticals, 2021)
New derivatives were synthesised by reaction of amino-containing aromatic sulphonamides with mono-, bi-, and tricyclic anhydrides. These sulphonamides were investigated as human carbonic anhydrases (hCAs, EC 4.2.1.1) I, II, IX, and XII inhibitors. hCA I was inhibited with inhibition constants (Kis) ranging from 49 to >10,000 nM. The physiologically dominant hCA II was significantly inhibited by most of the sulphonamide with the Kis ranging between 2.4 and 4515 nM. hCA IX and hCA XII were inhibited by these sulphonamides in the range of 9.7 to 7766 nM and 14 to 316 nM, respectively. The structure–activity relationships (SAR) are rationalised with the help of molecular docking studies.